Can ADMA play a role in determining pulmonary hypertension related to chronic obstructive pulmonary disease?. (11th August 2017) - Telo, Selda; Kırkıl, Gamze; Kuluöztürk, Mutlu; Balin, Mehmet; Deveci, Figen
Abstract: Background and aims: Asymmetric dimethylarginine (ADMA) decreases the levels of nitric oxide by inhibiting nitric oxide synthases. In this study, the possible role of ADMA in determining pulmonary hypertension (PH) in chronic obstructive pulmonary disease (COPD) patients was investigated. Methods: Stable COPD patients who were admitted to pulmonology outpatient clinic were involved in the study. Forty healthy volunteers, with similar ages and sexes, were accepted as the control group. COPD patients were divided into two groups: 40 patients without PH (COPD group) and 40 COPD‐related PH patients (COPD‐PH group). Pulmonary function test, echocardiography and arterial blood analyses of all patients were performed. Results: The mean age of patients was 69.21 ± 10.62, and 15 of these patients were females. There was no significant difference between the two COPD groups in terms of age and sex ( P > .05). There was no difference in PaO2, SaO2, FEV1 and FEV1 /FVC values between the two COPD groups ( P > .05). Serum ADMA levels were similar in the control and the COPD group (0.42 ± 0.13 vs 0.43 ± 0.15), but it was significantly higher in the COPD‐PH group compared to the control and the COPD group (0.49 ± 0.14). A negative correlation was determined between serum ADMA levels and SaO2 levels ( r = –.247, P = .028). A significant positive correlation observed between ADMA and systolic pulmonary artery pressure values ( r = .627, P < .001) Conclusions: In conclusion, high levels of serum ADMA levels may be able to determine the presence of PH.